Hubungan Antara Personal Growth Initiative dan Retensi Karyawan pada Generasi Z - Anggita Dian Cahyani; Michael Vierri (Bina Nusantara University, 2023)
Generation Z is one of the generations that has an important role in the world of work. In addition, with the development of the world of work, employee retention is one of the main challenges faced by companies to maintain company stability and sustainability. In order to maintain high retention of generation Z employees, companies need to understand the factors that influence them to remain in the organization. One factor that can affect the retention of generation Z employees is personal growth initiative. This study aims to analyze whether there is a significant relationship between the two variables. This study involved 100 participants who were generation Z who were already working. The design of this study is correlational, the data was taken using limesurvey and analyzed by product moment correlation analysis. The analysis results showed a positive relationship between personal growth initiative and employee retention (p = -0.00) with a value of r = 0.36. This research provides a better understanding of the importance of personal growth initiatives and their relationship to employee retention.